‘Breakpoint broth microdilution plate’ for susceptibility testing of Gram negative bacilli against colistin sulfate - Ahmed, Imran (Pract Lab Med, 2020)
The MIC method applicable to Gram negative bacilli including Acinetobacter spp. is broth microdilution (BMD). Cost and/or availability issues limit the use of commercial MIC panels in resource limited settings. OBJECTIVES: To design and implement an in-house breakpoint BMD panel (BBMD) for colistin against Gram negative bacilli. DESIGN: BBMD panel was prepared in 96-well plate. MIC concentrations of 1, 2, & 4 ​μg/mL for test, and 0.25, 0.5, 1, 2 & 4 ​μg/mL for control strains were selected to accommodate 19 test and 3 quality control strains per plate. Plates were frozen at −80 ​°C until testing. Validation was performed using strains from a previously published study and compared with freshly prepared MIC panel of 16–0.03 ​μg/mL. RESULTS: Validation showed 100% agreement with the reference method and BBMD was introduced into routine laboratory practice for colistin susceptibility of carbapenem resistant Enterobacterales (CRE), Acinetobacter baumannii complex and Pseudomonas aeruginosa. From 2nd July-16th September 2018, a total of 1294 (mean 16.8 ​± ​5.5 isolates/day) clinical isolates were tested; 1157/1294 were reported (MIC ≤2 ​μg/mL) within 24-h, whereas 133 required resistance confirmation by full-range BMD. Resistance was confirmed for all but 24 isolates. These discrepancies were mostly due to contamination with bacterial genera inherently resistant to colistin. CONCLUSION: This BBMD plate is a high through-put and practical method that could reliably be utilized in a routine microbiology laboratory for colistin susceptibility testing of CRE, A. bauamanii complex and P. aeruginosa.